2007
DOI: 10.1007/s10535-007-0038-4
|View full text |Cite
|
Sign up to set email alerts
|

Influence of UV-B radiation on young triticale plants with different wax cover

Abstract: Ultraviolet-B radiation (biologically effective dose 2.6 kJ m -2 d -1 ) had negative influence on morphology and physiology of the young triticale plants. Plants exposed to UV-B were of lower height than control plants, their leaves were narrow, and the rate of net photosynthesis was decreased. The line RAH 336, which wax cover is lesser than that of traditional cultivar Magnat, was more susceptible to UV-B radiation, considering primary photosynthesis reactions, recorded by chlorophyll a fluorescence. An acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 23 publications
0
5
0
1
Order By: Relevance
“…Literature research revealed that applied doses of UV-B radiation vary widely, both in terms of daily dose applied (e.g. 12, 13·3, 24, 49, 2·6 or 4·9 kJ/m 2 ) and duration of radiation treatment in general, ranging from 4 days to 12 weeks (Burchard et al 2000; Hofmann et al 2000; Nogues & Baker 2000; Alexieva et al 2001; Skórska & Szwarc 2007; Calderini et al 2008; Majer & Hideg 2012). The UV-B radiation reaching the earth's surface is much smaller than UV-A due to atmospheric depletion, but in the shorter wavelength of the UV-B region many biological responses are far greater (Madronich et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Literature research revealed that applied doses of UV-B radiation vary widely, both in terms of daily dose applied (e.g. 12, 13·3, 24, 49, 2·6 or 4·9 kJ/m 2 ) and duration of radiation treatment in general, ranging from 4 days to 12 weeks (Burchard et al 2000; Hofmann et al 2000; Nogues & Baker 2000; Alexieva et al 2001; Skórska & Szwarc 2007; Calderini et al 2008; Majer & Hideg 2012). The UV-B radiation reaching the earth's surface is much smaller than UV-A due to atmospheric depletion, but in the shorter wavelength of the UV-B region many biological responses are far greater (Madronich et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Epicuticular wax variability in triticale and its impact on cuticular transpiration has not been sufficiently investigated. Difference in epicuticular wax between two triticale varieties was associated with UV-B radiation tolerance, where the high wax cultivar was relatively more resistant (Skórska and Szwarc 2007). Saulescu et al (2011) concluded that rye and triticale had higher albedo than most wheat cultivars and they considered these species as genetic resources for improving this trait in wheat.…”
Section: Droughtmentioning
confidence: 99%
“…Protective responses stimulated by UV-radiation include increase in production of UV-absorbing compounds and secondary compounds including hydroxyl cinnamic acid derivatives, phenylpropanoids, and flavonoids which effectively absorb the UV-radiation (Hofmann et al 2000, Skórska andSzwarc 2007). Anthocyanins also have a wide distribution in mature and senescent leaves.…”
mentioning
confidence: 99%